2015
DOI: 10.1111/neup.12204
|View full text |Cite
|
Sign up to set email alerts
|

Isopentenyl diphosphate isomerase, a cholesterol synthesizing enzyme, is localized in Lewy bodies

Abstract: Isopentenyl diphosphate isomerase (IDI) is a cytoplasmic enzyme involved in the biosynthesis of isoprenoids including cholesterols. IDI has two isoforms in humans: IDI1 and IDI2. Since lipids are known to be a component of Lewy bodies (LBs), we investigated the immunohistochemical localization of IDI1 and IDI2 in the brain of patients with LB disease and multiple system atrophy (MSA) and normal control subjects. In normal controls, the cytoplasm of neurons was weakly immunostained with anti-IDI1 and anti-IDI2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Furthermore, TIGAR incorporation into Lewy bodies was only seen in brainstem but not cortical Lewy bodies. This phenomenon has also been seen with respect to isopentenyl diphosphate isomerase (Nakamura et al, 2015),. This is unusual, as most Lewy body protein components are present in both brainstem and cortical Lewy bodies (e.g, alpha-synuclein , MAP-5 (Gai et al, 1996), HDAC6 , Parkin , cyclin dependent kinase 5 , synphilin-1 .…”
Section: Within Individual Brains We Found Variable Expression Of Tisupporting
confidence: 54%
“…Furthermore, TIGAR incorporation into Lewy bodies was only seen in brainstem but not cortical Lewy bodies. This phenomenon has also been seen with respect to isopentenyl diphosphate isomerase (Nakamura et al, 2015),. This is unusual, as most Lewy body protein components are present in both brainstem and cortical Lewy bodies (e.g, alpha-synuclein , MAP-5 (Gai et al, 1996), HDAC6 , Parkin , cyclin dependent kinase 5 , synphilin-1 .…”
Section: Within Individual Brains We Found Variable Expression Of Tisupporting
confidence: 54%
“…In PD patients, the cholesterol-synthesizing enzymes isopentenyl diphosphate isomerases 1 and 2 have been observed in LB from the SN of PD patients [518]. The natural cholesterol intermediate squalene seems to prevent toxicity in the striatum of 6-OHDA-treated mice [519], whereas α-synuclein accumulation enhances squalene production [242], which could be a cellular response to oxidative damage.…”
Section: Sterolsmentioning
confidence: 99%
“…It has been reported that cholesterol biosynthesis is decreased in fibroblasts from patients with PD owing to reduced β-Hydroxy β-methylglutaryl-CoA (HMG-CoA) reductase activity [81]. In addition, isopentenyl diphosphate isomerase, a cholesterol-synthesizing enzyme, is localized in Lewy bodies, proposing that cholesterol metabolites may play a role in the aggregation of α-synuclein, enhancing Lewy body formation [82].…”
Section: Alterations Of Cholesterol Metabolism In Pdmentioning
confidence: 99%